Modeled, multistage convection cooking of beef semitendinosus roasts to denature collagen and to optimize tenderness - T.H. Powell; Melvin C. Hunt; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1999)
In order to predict and establish cooking times and temperatures of beef to optimize tenderness and cooked yield, a computer model was developed utilizing heat and mass transfer theories. We cooked beef semitendinosus (eye of round) roasts in a forced-air convection oven using conventional or modeled, multistaged cooking. Conventional cooking was defined as cooking at 325EF to a core endpoint of 150EF. The model method was developed using a computer algorithm that predicted heat and moisture (mass) transfer during a three-stage cooking process that included preheating, holding, and finishing. The model was accurate in predicting actual cooking times and temperatures during cooking; temperature profile curves tracked closely between predicted and observed values. Roasts cooked by the modeled cooking regimen had lower Warner-Bratzler shear values than those cooked by conventional convection cooking. Collagen total unaltered fraction was lower (P<.05; 44 vs. 55%) and enzyme labile fraction was higher (56 vs. 45%, P<.05) in model cooked than in conventionally cooked samples. Cooking yield was not different for the modeled and conventional procedures. These results show that the modeled multi-stage cooking method was superior to the conventional cooking method.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Tenderness; Modeling; Cooking; Semitendinosus; Collagen